Arsenic trioxide inhibits tumor cell growth in malignant rhabdoid tumors in vitro and in vivo by targeting overexpressed Gli1. Issue 4 (25th January 2014) - Kerl, Kornelius; Moreno, Natalia; Holsten, Till; Ahlfeld, Julia; Mertins, Julius; Hotfilder, Marc; Kool, Marcel; Bartelheim, Kerstin; Schleicher, Sabine; Handgretinger, Rupert; Schüller, Ulrich; Meisterernst, Michael; et al.
<x xml:space="preserve">Abstract</x> Rhabdoid tumors are highly aggressive tumors occurring in infants and very young children. Despite multimodal and intensive therapy prognosis remains poor. Molecular analyses have uncovered several deregulated pathways, among them the CDK4/6‐Rb‐, the WNT‐ and the Sonic hedgehog (SHH) pathways. The SHH pathway is activated in rhabdoid tumors by GLI1 overexpression. Here, we demonstrate that arsenic trioxide (ATO) inhibits tumor cell growth of malignant rhabdoid tumors in vitro and in a mouse xenograft model by suppressing Gli1. Our data uncover ATO as a promising therapeutic approach to improve prognosis for rhabdoid tumor patients.